Stochastic simulation of the nonlinear kinetic equation with high-frequency electromagnetic fields - Andriash, A.V.; Bobylev, A.V.; Brantov, A.V.; Bychenkov, V.Yu.; Karpov, S.A.; Potapenko, I.F. (Вопросы атомной науки и техники, 2013)
A general approach to Monte Carlo methods for Coulomb collisions is proposed. Its key idea is an approximation of Landau-Fokker-Planck (LFP) equations by Boltzmann equations of quasi-Maxwellian kind. Highfrequency fields are included into consideration and comparison with the well-known results are given.